Strategi Penanganan Trafficking di Indonesia - Darwinsyah Minin (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: The crime of trafficking increases in Indonesia. It is caused by several factors such a proverty, lack of education, fraudulent, sexual harassment and economic problem. This research identifies several problem, namely; sexual harrasment in conflict areas, domestic violence, the force as sexual object, organized threat, baby trafficking and human rgan trading. The strategy done in dealing with the problem are the mprovement in monitoring, the strengthening of the law deffenders and other stake holders by increasing the prevention without forgotting the punishment. The Strategy in Dealing with Trafficking in Indonesia